A simple, fast, sensitive and robust LC-MS/MS bioanalytical assay for evaluating 7α-hydroxy-4-cholesten-3-one biomarker in a clinical program. (December 2016) - Yuan, Long; Luo, Yi; Kandoussi, Hamza; Ji, Qin C
Aim: Serum 7α-hydroxy-cholesten-3-one (C4) has been reported as a biomarker to assess CYP7A1 enzyme activity and bile acid synthesis. To support a clinical program, a sensitive and reliable assay without derivatization was required for the analysis of C4 in human serum.Methodology & results: A systematic approach was used to optimize mass spectrometry, LC and sample extraction conditions, therefore, significantly improved assay sensitivity, and achieved the required quantification limit without derivatization. A surrogate matrix approach was used to overcome the interference from endogenous C4. A stable isotope-labeled C4 was used as internal standard. The samples were extracted using a simple protein precipitation method with 2% formic acid in acetonitrile.Conclusion: A simple, fast, sensitive and robust UHPLC-MS/MS method for the quantification of 0.50 ng/ml C4 in 100 µl human serum was developed and fit for purpose validated. The method was successfully applied to the bioanalysis of C4 in a clinical study.